Employing an in vitro biosensor assay to investigate tau seeding kinetics within cases of sporadic Alzheimer disease and in a model of tauopathy: Developing topics. (7th December 2020) - Kamath, Tarun V; Commins, Caitlin; Klickstein, Naomi; Oakley, Derek; Hyman, Bradley T; Dujardin, Simon
Abstract: Background: Tauopathies such as Alzheimer's disease (AD) are characterized by tau aggregation in the brain (Kovacs, 2015). Recent studies have suggested that tau aggregation occurs via the trans‐synaptic spread of certain tau species and subsequent aggregation via contact between these seeds and non‐aggregated tau (Mudher et al., 2017). Tau seeds can be isolated from many sources, including the brains of humans with tauopathies and tau‐transgenic mice (Clavaguera et al., 2009; Holmes et al., 2014; Iba et al., 2013; Kaufman et al., 2016). Here, we aimed to understand if the kinetics of tau seeding could inform us on the properties of initial seeds. Method: Brain extracts containing tau seeds from 32 patients with sporadic AD and the rTg4510 mouse model of tauopathy were incubated with a well‐described FRET‐biosensor tau seeding assay. The cells were imaged for 48 hours and analyzed for aggregate count and morphology. Result: Aggregate formation followed a logistic function over time, with a lag phase, exponential rise phase, and plateau phase. We investigated the properties of these phases by increasing the concentration of tau seeds added to the assay, which led to a parallel increase in the magnitude of the plateau phase and slope of the exponential rise phase, until a ceiling. Across cases of sporadic AD, the length of the lag phase was inversely correlated with the magnitude of the plateau phase. Finally, when initiating aggregation using tau seeds from the rTg4510 mouse, aggregation was several fold higher in the plateau phase than any case of sporadic AD, with significantly altered aggregate morphology which was not observed across the human AD aggregates. Conclusion: The definition of a strain of tau has long been dominated by structural variation – aggregates with different morphologies are thought to be of different strains (Sanders et al., 2014; Kaufman et al., 2016). We present here an alternative method of classifying aggregates based not just on morphology but on aggregation kinetics which we believe reflect biochemical and biophysical properties. This analysis reveals that contrary to previous reports, within cases of sporadic Alzheimer's disease, there may exist multiple strains of tau leading to variations in aggregate formation kinetics.